Factors Influencing Tax Evasion among Small and Medium Enterprises in Zimbabwe - Banele Dlamini (New Advances in Business, Management and Economics Vol. 5, 2025)
This paper aims to establish the major determinants of tax non-compliance among SMEs in the Zimbabwean economy. Small and medium-scale enterprises (SMEs) are recognized globally for being the backbone of the economy through economic advancement, innovation, wealth generation, and further growth. SMEs have a high tax non-compliance rate, which hinders the development brought to many economies. The survey research design was used, and the SMEs operating in Bulawayo province were considered the sample of the study. The stratified random sampling technique was adopted for eliciting information, and questionnaires were administered to collect data from the respondents. 187 questionnaires were issued, and 153 were returned. Regression analysis was used to establish the relationship between tax non-compliance and the predictive variables using SPSS version 22. Three main models of tax compliance were reviewed in the literature, and strong evidence of tax compliance determinants was provided. The study revealed poor follow-up strategy, lack of a tax audit, high tax rates, financial constraints, abuse of public funds by authorities, and tax education as the major determinants. SME operators should apply modern business survival strategies to counter financial limitations. ZIMRA should maintain a database for SMEs for tax audit purposes, intensify follow-up strategies, increase tax audits, and increase tax support services for SMEs. The government should consider reducing tax rates, which are perceived to be too high, as they promote tax evasion and failure among SMEs. Massive campaigns against evasion and avoidance of tax and intensive tax education should be embarked on.